Entrevista - Leonard Talmy - Abreu, Helen de Andrade (Programa de Pós-graduação em Linguística da Universidade Federal do Rio de Janeiro (UFRJ), 2016)
Leonard Talmy is Professor Emeritus of Linguistics at the University at Buffalo, State University of New York, where he taught for 15 years and was Director of the Center for Cognitive Science for 14 years. He is now also a Visiting Scholar at the University of California, Berkeley, where he had received his Ph.D. in Linguistics.